Un episodio en la construcción narrativa de la historia de España: los traidores y la ‘pérdida de España’ / An Episode in the Narrative Construction of the History of Spain: The Traitors and the ‘Loss of Spain’ - Padín Portela, Bruno (Historiografías, 2017)
This paper examines the role of traitor’s figure in the narratives of the principal Historias Generales de España focusing upon the the Islamic conquest of 711. Starting by the Germanic legislative tradition, which associates the idea of treason with king’s figure, we shall study the evolution of historical account throughout centuries, where the Visigoths have always played the role of axis in the representation of Spanish identity. We shall also discussed the different types of treason, their importance in national constructions, and their impact on historiographical tradition, emphasizing in particular the stereotype of the Jews and their stigmatization as internal enemies for much of the history of Spain.Key WordsTreason, Muslim conquest, Visigoth kingdom, histories of Spain.ResumenEn este trabajo analizaremos el papel de la figura del traidor en los relatos de las principales Historias Generales de España, centrándonos en el episodio de la conquista musulmana de 711. Partiendo de la tradición legislativa germánica, que asocia la idea de traición con la figura del rey, estudiaremos la evolución del relato histórico a través de los siglos, donde los visigodos jugaron el papel de eje vertebrador de la identidad española. Reflexionaremos también sobre los diferentes tipos de traiciones, su importancia en los relatos de las construcciones nacionales, y su impacto en la tradición historiográfica; poniendo el acento en el estereotipo de los judíos y su estigmatización como enemigos internos durante gran parte de la historia de España.Palabras claveTraición, conquista musulmana, reino visigodo, historias de España.